Amyloid-beta peptide decreases expression and function of glutamate transporters in nervous system cells. (April 2017) - Tong, Huichun; Zhang, Xiuping; Meng, Xingjun; Xu, Pingyi; Zou, Xiaoming; Qu, Shaogang
Abstract: Glutamate is an essential excitatory neurotransmitter that regulates brain functions, and its activity is tightly regulated by glutamate transporters. Excess glutamate in the synaptic cleft and dysfunction of excitatory amino acid transporters have been shown to be involved in development of Alzheimer's disease, but the precise regulatory mechanism is poorly understood. Using a D-[ 3 H]-aspartic acid uptake assay, we found that Aβ1-42 oligomers impaired glutamate uptake in astrocytes and neurons. In astrocytes, this process was accompanied by reduced expression of GLT-1 and GLAST as detected by Western blot and immunocytofluorescence. However, mRNA levels of EAATs detected by qPCR in astrocytes and neurons were not altered, which suggests that this process is post-translational. Co-localization analysis using immunocytofluorescence showed that ubiquitylation of GLT-1 significantly increased. Therefore, we hypothesized that Aβ1-42 oligomers-induced endocytosis of astrocytic GLT-1 may be involved in ubiquitylation. In addition, Aβ1-42 oligomers enhanced secretion of IL-1β, TNF-α, and IL-6 into culture supernatant, which may be correlated with an inflammatory response and altered EAATs expression or function in Alzheimer's disease. These findings support the idea that dysregulation of the glutamatergic system may play a significant role in pathogenesis of Alzheimer's disease. Furthermore, enhancing expression or function of EAATs in astrocytes and neurons might be a new therapeutic approach in treatment of Alzheimer's disease.